Clelia rustica (Jan, 1863) (Serpentes: Dipsadidae): distribution extension - Perez, Cristian Hernan Fulvio (2012)
A new record of the snake Clelia rustica is reported for the province of Neuquén in northwestern Patagonia, extending the distribution by more than 200 km north from previous records; it was known before only from the southernmost regions of the province.